Effect of a 2 versus 3 times per week weight training program in boys aged 7 to 16 - Stahle, S. D.; Roberts, S. O.; Davis, B.; Rybicki, L. A. (Medicine & Science in Sports & Exercise, 1995)
It was found that weight training two times per week was equally effective for developing strength as was three times. Implication: In growing children and youths, there is no need to do a "lot" of weight-training. Two times per week appears to be quite sufficient to develop significant changes. More frequent sessions do not produce any more development.